Analgesia Multimodal Pascaoperatif pada Pasien Pediatrik - Widyastuti, Yunita; Sari, Djayanti; Rizki, Gilar (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Acute pain can be found in patient undergoing surgery. Postoperative pain scale is variable from mild to moderate-severe. There are difficulties in assessing pain scale in pediatric, not like adult, pediatric patient can’t say what they feel. Management of postoperative pain, especially in moderate-severe scale needs a multimodal approach to overcome it. The aim of multimodal strategy is to optimize analgetic effect and reduce the adverse effect of the drugs.